Reducing Writing Anxiety through Digital Storytelling: Insights from Junior High School EFL Learners - Furi, Sitti Aisyah Ratna; Arifin, Syaadiah; Ilyas, Hamzah Puadi (PROJECT (Professional Journal of English Education), 2025)
This study investigates the digital storytelling roles in lessening writing anxiety among junior high school students learning English as a foreign language (EFL). Writing anxiety is a common challenge that affects students' ability to express themselves effectively. The purpose of this research is to explore how digital storytelling, which combines multimedia elements like images, sound, and video, can alleviate anxiety and improve writing skills. The study used a mixed-method approach, involving both quantitative data from the Second Language Writing Anxiety Inventory (SLWAI) and qualitative insights from interviews. Findings reveal that before the intervention, students experienced moderate to high levels of anxiety. After using digital storytelling, anxiety levels significantly decreased, especially among male students, with reductions in cognitive and somatic anxiety, as well as avoidance behaviours. Qualitative data further supported these findings, showing that students felt more motivated, engaged, and confident in their writing. Digital storytelling helped students improve their writing skills, increase their error awareness, and foster a sense of ownership and creativity. The study suggests that digital storytelling can be a valuable pedagogical tool to create a less intimidating learning environment and enhance writing proficiency in EFL classrooms. However, further exploration is needed to understand the differing impacts on male and female students.